The West African monsoon dynamics, Part II : The "pre-onset" and the "onset" of the summer monsoon - (:unkn) unknown (My University, 2003)
The arrival of the summer monsoon over West Africa has been documented by using daily gridded rainfall data and NCEP-NCAR reanalyses during the period 1968-90, and OLR data over the period 1979-90. Two steps have been characterized through a composite approach: the preonset and the onset of the summer monsoon. The preonset stage corresponds to the arrival in the intertropical front (ITF) at 15ЊN, that is, the confluence line between moist southwesterly monsoon winds and dry northeasterly Harmattan, bringing sufficient moisture for isolated convective systems to develop in the Sudano-Sahelian zone while the intertropical convergence zone (ITCZ) is centered at 5ЊN. The mean date for the preonset occurrence is 14 May and its standard deviation is 9.5 days during the period 1968-90. This leads to a first clear increase of the positive rainfall slope corresponding to the beginning of the rainy season over this Sudano-Sahelian area. The onset stage of the summer monsoon over West Africa is linked to an abrupt latitudinal shift of the ITCZ from a quasi-stationary location at 5ЊN in May-June to another quasi-stationary location at 10ЊN in July-August. The mean date for the onset occurrence is 24 June and its standard deviation is 8 days during the period 1968-90. This leads to a second increase of the positive rainfall slope over the Sudano-Sahelian zone signing the northernmost location of the ITCZ and the beginning of the monsoon season. This abrupt shift occurs mostly between 10ЊW and 5ЊE, where a meridional land-sea contrast exists, and it is characterized by a temporary rainfall and convection decrease over West Africa. Preonset dates, onset dates, and summer rainfall amount over the Sahel are uncorrelated during the period 1968-90. The atmospheric dynamics associated with the abrupt ITCZ shift has been investigated. Between the preonset and the onset stages, the heat low dynamics associated with the ITF controls the circulation in the low and midle
Keywords: African Research